In situ growth of WO3/BiVO4 nanoflowers onto cellulose fibers to construct photoelectrochemical/colorimetric lab-on-paper devices for the ultrasensitive detection of AFP. Issue 21 (4th May 2022) - Li, Xu; Cui, Kang; Xiu, Mingzhen; Zhou, Chenxi; Li, Li; Zhang, Jing; Hao, Shiji; Zhang, Lina; Ge, Shenguang; Huang, Yizhong; Yu, Jinghua
Abstract : A dual-mode lab-on-paper device for sensitive photoelectrochemical/colorimetric sensing of AFP based on in situ grown WO3 /BiVO4 heterojunctions onto cellulose fibers. Abstract : In this work, novel dual-mode lab-on-paper devices based on in situ grown WO3 /BiVO4 heterojunctions onto cellulose fibers, as signal amplification probes, were successfully fabricated by the integration of photoelectrochemical (PEC)/colorimetric analysis technologies into a paper sensing platform for the ultrasensitive detection of alpha-fetoprotein (AFP). Specifically, to achieve an impressive PEC performance of the lab-on-paper device, the WO3 /BiVO4 heterojunction was in situ grown onto the surface of cellulose fibers assisted with Au nanoparticle (Au NP) functionalization for enhancing the conductivity of the working zone of the device. With the target concentration increased, more immune conjugates could be captured by the proposed paper photoelectrode, which could lead to a quantitative decrease in the photocurrent intensity, eventually realizing the accurate PEC signal readout. To meet the requirement of end-user application, a colorimetric signal readout system was designed for the lab-on-paper device based on the color reaction of 3, 3′5, 5′-tetramethylbenzidine (TMB) oxidized by WO3 /BiVO4 nanoflowers in the presence of H2 O2 . Noticeably, it is the first time that the WO3 /BiVO4 heterojunction is in situ grown onto cellulose fibers, which enhances the sensitivity in view of both their PEC activity and catalytic ability. By controlling the conversion process of hydrophobicity and hydrophilicity on the lab-on-paper device combined with diverse origami methods, the dual-mode PEC/colorimetric signal output for the ultrasensitive AFP detection was realized. Under optimal conditions, the proposed dual-mode lab-on-paper device could enable the sensitive PEC/colorimetric diagnosis of AFP in the linear range of 0.09–100 ng mL −1 and 5–100 ng mL −1 with the limit of detection of 0.03 and 1.47 ng mL −1, respectively.